Faktor Perilaku Yang Berhubungan dengan Kejadian Hipertensi di Puskesmas Serpong I, Kota Tangerang Selatan: Behavioral Factors Associated with the Incidence of Hypertension at Serpong I Primary Health Care, South Tangerang City - Muhammad Nurul Raditya; Rony Darmawansyah Alnur (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Background: Hypertension is frequently regarded as a significant health concern. This is corroborated by the annual increase in hypertension cases. Behavioral factors, including smoking, physical activity, consumption of salty foods, and consumption of fatty foods, have been identified as risk factors for hypertension. Objective: The objective of this study is to examine the behavioral factors associated with the incidence of hypertension at the Serpong I Primary Health Care in South Tangerang City in 2024. Methods: The study employed a quantitative research design with a cross-sectional study structure and an analytic approach, utilizing the Chi-square test was conducted to examine the relationship between the independent variables and the incidence of hypertension. The study was conducted over a period of six months, from February to August 2024. The population under investigation in this study consisted of all individuals who visited the Serpong I Primary Health Care in South Tangerang City. The sample size for this study was 101 individuals, selected using the purposive sampling technique. The data were subjected to univariate and bivariate analyses. Results: The frequency distribution demonstrated that a greater proportion of respondents did not smoke (74, 73.3%), engaged in sufficient physical activity (72, 71.3%), consumed excessive amounts of salty foods (53, 52.5%), and consumed fatty foods (53, 52.5%). The results of the Chi-square test indicate that the variable most strongly associated with the incidence of hypertension (Pvalue <0.05) is the consumption of salty foods (P-value <0.001). While variables that are not associated (Pvalue > 0.05) include smoking (Pvalue = 0.661), physical activity (Pvalue = 0.173), and consumption of fatty foods (Pvalue = 0.079). Conclusion: The findings indicate a correlation between excessive sodium consumption and the prevalence of hypertension at the Serpong I Primary Health Care in South Tangerang in 2024. It is recommended that respondents to reduce the consumption of foods with high sodium content. Keywords: Hypertension; Risk Factors; Behavior;Primary Health Care.